Pearla and her unpredictably perfect day : a story about how a sprinkling of mistakes can be a recipe for success - Lieberman, Rochel (Jessica Kingsley Pub., 2017)
"Pearla loves to bake! Her favorite foods are cookies and cupcakes, which she sells at her dad's bakery. She always tries very hard to make her baking absolutely perfect, but one day Pearla is so busy that she makes a huge mistake! Have fun with Pearla as she learns how to adapt when her day doesn't go to plan and realizes it could turn out to be pretty perfect after all. This is a scrumptious tale for children aged 4-12, particularly those who experience anxiety or developmental issues."-- back cover